2021
DOI: 10.1186/s13195-021-00854-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying novel genetic variants for brain amyloid deposition: a genome-wide association study in the Korean population

Abstract: Background Genome-wide association studies (GWAS) have identified a number of genetic variants for Alzheimer’s disease (AD). However, most GWAS were conducted in individuals of European ancestry, and non-European populations are still underrepresented in genetic discovery efforts. Here, we performed GWAS to identify single nucleotide polymorphisms (SNPs) associated with amyloid β (Aβ) positivity using a large sample of Korean population. Methods On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, summary statistics data was obtained from six additional cohorts that processed the raw genotype and phenotype data according to the same pipeline. These cohorts included Memento [ 24 ], Mayo Clinic Study of Aging (MCSA) [ 25 ], Wisconsin Registry for Alzheimer's Prevention (WRAP) [ 26 ], Berkeley Aging Cohort study (BACS) [ 27 ], Korean study [ 28 ], and MISSION-AD. Part of the data used in the preparation of this article was obtained from the ADNI database (adni.loni.usc.edu).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, summary statistics data was obtained from six additional cohorts that processed the raw genotype and phenotype data according to the same pipeline. These cohorts included Memento [ 24 ], Mayo Clinic Study of Aging (MCSA) [ 25 ], Wisconsin Registry for Alzheimer's Prevention (WRAP) [ 26 ], Berkeley Aging Cohort study (BACS) [ 27 ], Korean study [ 28 ], and MISSION-AD. Part of the data used in the preparation of this article was obtained from the ADNI database (adni.loni.usc.edu).…”
Section: Methodsmentioning
confidence: 99%
“…A subset of 1214 participants in data set 1 underwent either 18F-florbetaben or 18F-flutemetamol PET (eMethods in the Supplement ). 20 Aβ positivity was determined by visual assessments.…”
Section: Methodsmentioning
confidence: 99%
“…FERMT2 gene had a stage-dependent association with brain amyloidosis 2018 Scelsi et al [ 79 ] ADNI (226 HC, 125 AD, 92 SMC, 501 MCI) Genome-wide genotyping Multivariate imaging—Multivariate genetic PGS-based association Aβ PET SUVR, HV Hippocampus The finding identified a genome-wide significant locus implicating LCORL rs6850306. The possession of a minor allele at rs6850306 was protective against conversion from MCI to AD 2019 Li et al [ 80 ] ADNI (155 HC, 125 AD, 72 SMC, 422 MCI) Genome-wide genotyping Univariate imaging—Multivariate genetic GWAS Florbetapir composite SUVR Frontal, anterior/ posterior cingulate, lateral parietal/ temporal regions The study identified 24 consensus modules enriched by robust genetic signals in a genome wide association analysis, including a few novel genes ( ABL1 , ABLIM2 ) 2021 Kim et al [ 81 ] Korean cohort ( n = 1474) Genome- wide genotyping Univariate imaging—multivariate genetic GWAS Aβ PET SUVR Whole brain In addition to APOE , nine SNPs of FGL2 gene on chromosome 7 were identified, which were associated with a decreased risk of Aβ positivity at a genome-wide suggestive level 2021 Liu et al [ 82 ] Multiple cohorts ( n = 767/ 1373) Summary statistics Multivariate imaging—Multivariate genetic PGS-based association Aβ PET SUVR, HV, entorhinal, middle temporal gyrus volumes Whole brain cortex, Hippocampus, entorhinal cortex PGS was associated with the increased cortical amyloid burdens (PiB-PET and AV45-PET), but decreased hippocampus and entorhinal cortex volumes …”
Section: Implementation Of Ad Imaging Biomarker Genomics Studiesmentioning
confidence: 99%